Design of monitoring and control system for water bursting in floor of coal seam - LI Cai-ping; ZHANG Ying-mei; ZHANG Zhen-guo (Gong-kuang zidonghua, 2013)
In order to solve problems of existing water bursting prevention methods such as large difference between theoretical parameters and actual environmental parameters, poor advanced forecast and real-time performance and so on, the paper proposed a design scheme of monitoring and control system for water bursting in floor of coal seam based on video monitoring, and emphatically introduced image processing algorithm of the system taking a water bursting accident in a coal mine as an example. The system obtains boundary point coordinates of water bursting image by use of digital image processing technology including graying, image enhancement, binaryzation, image segmentation and edge feature extraction, does curve fitting processing for the boundary point coordinates to get water bursting area, and judges change trend of water bursting according to the difference of the water bursting area at different time. The test run showed that the system is reliable with clear video image and effective image processing algorithm and can timely warn when water bursting is abnormal.